Quality of Winter Barley Grain from the Testing Localities in the Czech Republic, Harvest 2014 - Lenka Sachambula; Vratislav Psota; Olga Dvořáčková (Kvasný průmysl, 2016)
Samples of two studied winter barley varieties from 13 testing localities were analyzed according to the standard ČSN 46 1100-5. Based on the standard, sieving fractions over 2.5 mm, total admixtures, admixtures non-usable for malting, admixtures partly usable for malting, grains without hulls, grains with black tips and grains with the awn were assessed. Contents of nitrogenous substances and starch were 10.8 % and 63.9 %, respectively. Grain harvested in 2014 was bigger and even in size. Sieving fractions over 2.5 mm moved on average around 91.6 %. The year 2014 in terms of barley grain quality was very favorable, there was no problem with sprouting, the occurrence of admixtures was the lowest in last three years and the admixtures were mostly partly usable for malting.